PENGARUH INOKULASI RHIZOBIUM TERHADAP PERTUMBUHAN TANAMAN KEDELAI (Glycine max L) VARIETAS WILIS DI RUMAH KACA - Sri Purwaningsih (BERITA BIOLOGI, 2015)
Effect of Rhizobium inoculation on the growth of Glycine max L. Wilis variety was endicated based on green house experiment.The aim of the experiment was to asses the potency of the Rhizobium strain to inccrease the growth of Glycine max L.Strains of : 1 WG, 1 WS, 1 P, 16 GH, 1 LS, 1 BK, 1 KT, 1 BR, and 11 WY were used in this research. Controls treatment were uninoculated with Rhizobium strain -1 and without urea fertilizer (K1) and uninoculated and with urea fertilizer equal 100 kg ha (K2). The research design was Completely Randomized Design with three replications for each treatment.Experiment plants were harvested after 50 days.Parameters of investigation were the dry weight of canopy, roots, nodules root, total plants, number of nodules, and “Symbiotic Capacity”.Results of this studies showed all of the Rhizobium inoculants able to form nodule. Strain 1 KT (isolate of soil from Kalampangan, Palangkaraya,Central Kalimantan) has given the best results on the growth of Glycine max L.